Weed Ecology and New Approaches for Management (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Satisfying consumer needs through the production of healthy and nutritious agricultural products is a substantial challenge facing modern agriculture. However, agricultural production should be carried out with care for plant health, biological safety of products, and environmental safety while minimizing the risks to human health. Therefore, the implementation of agricultural practices while respecting these principles is very important for improving the quantity and quality of crops. Additionally, ecosystems have been altered as a result of human activities and climate change, resulting in the reduction of biodiversity and creation of new niches where pests can thrive. This is of particular importance in 2020, as the United Nations General Assembly declared this year as the International Year of Plant Health (IYPH), with “protecting plants, protecting life” as a leading subject.This Special Issue promotes the subject of plant health and emphasize the importance of preventing the spread of pests, including weeds, which cause substantial economic losses. Research articles cover topics related to the biology and harmfulness of weeds, particularly in connection with crop health, segetal weed communities and their biodiversity, and integrated methods of weed control. For this Special Issue, we welcome all types of articles, including original research, opinions, and reviews.